Tubular Duplication of the Esophagus in a Newborn, Treated by Thoracoscopy - Khvorostov, Igor; Gusev, Alexey; Alkhasov, Abdumanap; Yatsyk, Sergey; D'yakonova, Elena (European Journal of Pediatric Surgery Reports, 2022)
We present a case of tubular esophageal duplication in a 3-day-old female newborn (38 weeks, 2,500 g) without concomitant abnormal development. Esophageal duplication was diagnosed based on the clinical picture, direct laryngoscopy, esophagography and computed tomography. The duplicated esophagus was resected by thoracoscopy leaving the orthotopic esophagus in place. Isolation from the pharynx was performed via a separate cervical incision. After a follow-up period of 20 months, the child returned to normal growth and development.
Keywords: esophageal duplication; newborn; thoracoscopy